Sepsis Pseudomonas Aeruginosa pada Pasien Chronic Kidney Disease: A Case Report - Angriani, Novita; Sommeng, Faisal; Wahab, Iswan (Universitas Pahlawan Tuanku Tambusai, 2025)
Sepsis is a life-threatening condition resulting from the body's systemic response to infection that causes organ dysfunction. Early diagnosis and prompt treatment are essential to improve patient outcomes. This case report aims to describe the management of sepsis in a 55-year-old male patient diagnosed with antibiotic-resistant Pseudomonas aeruginosa infection. This retrospective study analyzed the patient's clinical and laboratory data, including blood culture, SOFA score, and therapeutic interventions given. The patient was given hemodialysis, broad-spectrum antibiotics, vasopressors, intravenous fluids, and supportive care. The results showed significant improvement in the patient's clinical status, supporting the importance of early recognition, appropriate antibiotic therapy, and a multidisciplinary approach in the management of sepsis. This case highlights the challenges of managing infections caused by multidrug-resistant pathogens and the importance of effective treatment strategies and judicious antibiotic management.